Legal Analysis of The Criminal Acts of Village Fund Budget Corruption (Study of The Simalungun District Prosecutor's Office - Reza Fikri Dharmawan; Rahmayanti Rahmayanti; Suci Ramadani (Journal of Research in Social Science and Humanities, 2025)
This research, entitled “A Juridical Analysis of Village Fund Corruption Crimes (A Case Study at the Simalungun District Prosecutor’s Office),” is motivated by the increasing number of cases involving the misuse of village funds that have caused state financial losses and eroded public trust in village governments. The study aims to analyze how the law is applied in cases of village fund corruption handled by the Simalungun District Prosecutor’s Office, to identify the obstacles encountered by prosecutors in handling such cases, and to evaluate the effectiveness of law enforcement in eradicating corruption involving village funds. The research adopts a normative juridical method using statutory, conceptual, and case approaches, focusing on the Kardianto case handled by the Simalungun District Prosecutor’s Office. The data sources consist of primary legal materials, such as legislation and indictment documents; secondary legal materials, including books, journals, and previous research; and tertiary legal materials, such as legal dictionaries and encyclopedias. The findings reveal that the application of law in cases of village fund corruption has been carried out in accordance with Law No. 31 of 1999 in conjunction with Law No. 20 of 2001 on the Eradication of Corruption Crimes and Law No. 6 of 2014 on Villages. However, the effectiveness of law enforcement remains hindered by overlapping regulations, limited human resources, weak inter-agency coordination, and low levels of legal awareness among the community. Nevertheless, the Simalungun District Prosecutor’s Office has demonstrated progressive measures through the implementation of the Jaksa Garda Desa (Village Guardian Prosecutor) program and the digitalization of public-fund monitoring. The study concludes that law enforcement against village fund corruption in the jurisdiction of the Simalungun District Prosecutor’s Office has been relatively effective in its repressive aspects but needs strengthening in preventive and participatory dimensions. Institutional reform, capacity building for law enforcement officers, and active community participation are essential to establishing transparent, accountable, and corruption-free village governance.